Representations of women in the poetry of Khalil Hawi - Shararah, Murtadha Ali (Journal of Humanities & Social Sciences, 2021)
This research aims to address the representations of women in the poetry of Khalil Hawi, and to prove their multiplicity and diversity, and that they are closely related to the poet’s personal and ideological life. The research followed the descriptive and analytical method, in investigating the subject in question, clarifying it and supporting it with poetic evidence. The research ended with a set of results according to which women had a remarkable presence in Khalil Hawi’s poetry, through a group of representations, Hawi succeeded in dealing with them objectively and artistically. The most prominent of these representations were: the mother woman and the beloved woman. Hawi was able to take this issue to broad symbolic horizons affecting the national issue that plagued him throughout his life.